ChemInform Abstract: Phosphoric Acid‐Mediated Synthesis of Vinyl Sulfones Through Decarboxylative Coupling Reactions of Sodium Sulfinates with Phenylpropiolic Acids. Issue 47 (November 2015) - Rong, Guangwei; Mao, Jincheng; Yan, Hong; Zheng, Yang; Zhang, Guoqi
Abstract: under catalyst‐free and green reaction conditions